Evaluating the Composition of the Microorganism Community Found in the Soil Cover on the Dried Seabed of the Aral Sea - Stulina, Galina; Verkhovtseva, Nadejda; Gorbacheva, Maria (Scientific Research, New Technologies and Applications Vol. 5, 2024)
The drying up of the Aral Sea and the occurrence of a vast desert in its place has been recognized as the world’s century catastrophe! More than 2 km of the seabed becomes exposed every year. As a result of the Aral Sea shrinkage, the unique freshwater body has given place to a huge bitter-saline lake with an area 3.5 times less, volume 6 times less and water salinity 10 times larger than in 1960, and the saline desert at the interface between three sand deserts with an area of more than 5 million ha, being unstable ecological zone. The exposed ground serves as an example of an arid salt accumulation where a particular kind of coastal solonchak soil was produced. The beginning of life in the dried bed's soil occurs far earlier than the development of outward features. The only way to track this process is to examine the soil's microbial makeup. To ascertain the microbial makeup of soil for horizons of a single typical solonchak profile, research in this area was carried out. The research objective was to determine microorganism species in the soil on the dried seabed and identify changes in the microorganism community along the soil profile and dependence on the duration of the drying process. Additionally, attention was paid to a vegetation effect on the composition of microorganisms. Soil samples were taken along a transect from the sea to the mainland, selected from the different depths of soil profiles taken under or near plants (Saxaul). Then quantitative and qualitative assessment of microorganisms was made by a molecular method against fatty acids (FA), aldehydes, and hydroxy fatty acids, and microorganisms were reconstructed against these markers to genus and even species in some cases. The method of Gas chromatography mass-spectrometry was used. Bacteria of the community of microorganisms in different parts of the soil cover on the dried seabed of the Aral Sea and on the mainland belong to five bacterial phyla: Proteobacteria Actinobacteria Firmicutes Bacteroidetes and Deinococcus-Thermus. In general, 59 bacterial species of 43 genera were reconstructed. The total population varied from 105 cells/g to 108 cells/g of the soil. The association Aeromonas hydrophila-Arthrobacter sp. played a key role in the first stages of the soil formation process on the dried seabed of the Aral Sea. This association is followed by salt-resistant Agrobacterium sp. and humus-accumulating Propionibacterium freudenreichii, the activity of which is also very important for the formation of the soil cover. The research showed that unique processes that are of great scientific interest take place on the dried bed of the Aral Sea. The studying properties of the dried seabed cover of both salt composition and microbiological composition made it possible to trace the formation of primary soil on marine sediments with the subsequent formation of desert-type soil. The research on soil cover development will help to understand the kernel of the desertification process as a whole from a microbiological standpoint.